Konsep Sabar dalam Perspektif Ulama Tafsir - Rahmawati, Lilis (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2023)
Patience is a word that is easy to say but difficult to practice. Patience is refraining from everything that Allah hates or being steadfast in accepting all His decrees and surrendering to Him. Therefore, Islamic law encourages its people to always hold back (be patient) with the things or events they are facing. Patience is refraining from carrying out desires and leaving things that are forbidden by Allah swt. The purpose of this research is to find out the interpretation of surah Al-Baqarah verses 155-157 perspective of the scholars to find out how to be patient in facing the trials of life. The research method that will be used in this research is descriptive method. The type of research used in this study is a type of library research. The data analysis technique that will be used in this study is a content analysis technique. The results of this study are that being patient in facing life's tests is one of God's ways to make His servants more grateful for what they face. Recommendations from the author, hopefully future researchers can reproduce and strengthen the results of this study.Keywords: Patience, Tests, Al-Qur’an.